1997
DOI: 10.1364/ol.22.000419
|View full text |Cite
|
Sign up to set email alerts
|

Al wire-grid polarizer using the s-polarization resonance effect at the 08-µm-wavelength band

Abstract: An aluminum wire-grid polarizer whose period is 0.39 microm has been fabricated on a quartz substrate by electron-beam direct-writing lithography and the lift-off method. By using the s -polarization resonance effect and optimizing structural parameters, characteristics such as a loss of less than 20% and an extinction ratio larger than 1000 have been experimentally obtained at the 0.8- microm -wavelength band. Theoretical analysis is performed and found to be consistent with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 6 publications
1
55
0
1
Order By: Relevance
“…In optics, a large variety of nanofabricated optical elements, such as ultrathin polarizers 1 and wave retarders, 2,3 nanostructured antireflection coatings, 4 optical waveguides, 5 plasmonic nanoantennas and nanosensors, 6 substrates for surface enhanced Raman scattering, 7 and optical metamaterials, 8 have been developed and demonstrated to find numerous useful applications. As a specific class of nanofabricated optical elements, we mention periodic arrays of metal nanostructures, which can be designed to have a prescribed, strong, and spectrally highly selective optical response.…”
mentioning
confidence: 99%
“…In optics, a large variety of nanofabricated optical elements, such as ultrathin polarizers 1 and wave retarders, 2,3 nanostructured antireflection coatings, 4 optical waveguides, 5 plasmonic nanoantennas and nanosensors, 6 substrates for surface enhanced Raman scattering, 7 and optical metamaterials, 8 have been developed and demonstrated to find numerous useful applications. As a specific class of nanofabricated optical elements, we mention periodic arrays of metal nanostructures, which can be designed to have a prescribed, strong, and spectrally highly selective optical response.…”
mentioning
confidence: 99%
“…All of the transmission spectra matched well with the color matching functions which were similar optical properties to human eyes. On the other hand, several researchers reported WGPs made of [4]. The extinction ratio larger than 1000 was experimentally obtained at the 0.8-μm-wavelength band.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, subwavelength gratings (SWGs) such as structural color filters [1][2][3], wire-grid polarizers (WGPs) [4][5][6][7][8], phase plates [9], and antireflection filters [10][11][12][13][14][15] attract a great deal of attention as highly functional low-loss filters. The SWGs have smaller periods than the operation wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…10 It would be commercially interesting to fabricate these grids directly in the CMOS process, but this limits the minimum pitch. Tamada et al 11 showed that efficient polarization properties can however be obtained in the resonant regime ͑i.e., p Ϸ ͒ by controlling both aperture width w and film thickness h.…”
mentioning
confidence: 99%
“…Increasing h consequently strongly reduces s-transmission. 11 For perfect metals, s-polarized modes are nonpropagating for Ͼ c , where c = w / 2 is the cutoff wavelength. c cannot be sharply defined for real metals due to their finite conductivity.…”
mentioning
confidence: 99%